Clifford's kitten - Bridwell, Norman (New York : Scholastic, Inc., 1985)
Clifford imitates all the antics of alittle kitten with hilarious -- and sometimes disastrous -- results.
3 7 13 20 21 23 26 27 29 30 31 36
Keywords: Dogs